2022
DOI: 10.1029/2021gl097034
|View full text |Cite
|
Sign up to set email alerts
|

Likely P‐to‐S Conversion at the Core‐Mantle Boundary Extracted From Array Processing of Noise Records

Abstract: Seismic noise has been widely used to image Earth's structure in the past decades as a powerful supplement to earthquake signals. Although the seismic noise field contains both surface‐wave and body‐wave components, most previous studies have focused on surface waves due to their large amplitudes. Here, we use array analyses to identify body‐wave noise traveling as PKP waves. We find that by cross‐correlating the array‐stacked horizontal‐ and vertical‐component data in the time windows containing the PKP noise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Such studies showed that for estimating seismic structures using P‐wave microseisms, considering their source locations is important. Back projection before cross‐correlation is one of the possible solutions for improved extraction (e.g., Liu & Shearer, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies showed that for estimating seismic structures using P‐wave microseisms, considering their source locations is important. Back projection before cross‐correlation is one of the possible solutions for improved extraction (e.g., Liu & Shearer, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies showed that for estimating seismic structures using P-wave microseisms, considering their source locations is important. Back projection before cross-correlation is one of the possible solutions for improved extraction (e.g., Liu & Shearer, 2022).…”
mentioning
confidence: 99%